REC-PATH (Recovery Pathways): Overview of a Four-Country Study of Pathways to Recovery from Problematic Drug Use. Issue 4 (2nd October 2018) - Best, David; Vanderplasschen, Wouter; Van de Mheen, Dike; De Maeyer, Jessica; Colman, Charlotte; Vander Laenen, Freya; Irving, Jamie; Andersson, Catrin; Edwards, Michael; Bellaert, Lore; Martinelli, Thomas; Graham, Simon; et al.
ABSTRACT: Although there has been a growth in recent years in recovery research, much of this has been from the United States, and there is very little comparative research in this area. This article describes the rationale, conceptual foundations and methods for a prospective, multicountry, cohort study aimed to map pathways to recovery from problematic illicit drug use, with a specific focus on gender differences in recovery pathways. This study combines qualitative and quantitative components and examines the impact of recovery policy on the accessibility and viability of recovery pathways in England, Scotland, Belgium, and The Netherlands. Additionally, the article describes five processes through which mechanisms for behavior change for recovery may be triggered. This study will provide opportunities for linking recovery outcome research with analyses of national recovery policies, while also addressing the gap in literature around female pathways to recovery.